Una mirada a las tendencias didácticas de la escritura creativa en español en la educación Básica y Media Colombiana (2017)
This compilation monograph was done through a methodology known as Qualitative Content Analysis, which served the purpose to identify and categorize the teaching and learning strategies about creative writing used in basic and middle education in Colombia. Monographs, doctoral and master dissertations, and articles published and available in databases and the internet were taken into account.